2004
DOI: 10.1159/000077360
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 2D6*10 C188T Polymorphism Is Associated with Antipsychotic-Induced Persistent Tardive Dyskinesia in Chinese Schizophrenic Patients

Abstract: Typical antipsychotic treatment had been postulated to be a risk factor for the susceptibility to tardive dyskinesia (TD). The cytochrome P-450 debrisoquine/sparteine hydroxylase (CYP2D6) metabolizes a majority of antipsychotics and exhibits various phenotypes on enzymatic activities from poor metabolizers to ultrarapid metabolizers. The various phenotypes are encoded by polymorphic genetic variants on the CYP2D6 gene. Although several studies had explored the association between the CYP2D6*10 C188T polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 24 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…221 CYP2D6 PM variants have been found associated with TD, EPS, AIMS scores and parkinsonism in several studies including different ethnic groups. 211,213,215,220 In a study in German patients, CYP2D6 genotype was as good a predictor of adverse events as plasma haloperidol concentrations, 217 and adds to the clinical value of CYP genotyping. CYP1A2 variants constitute genetic risk factors for the development of drug-induced TD as suggested by positive association findings.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…221 CYP2D6 PM variants have been found associated with TD, EPS, AIMS scores and parkinsonism in several studies including different ethnic groups. 211,213,215,220 In a study in German patients, CYP2D6 genotype was as good a predictor of adverse events as plasma haloperidol concentrations, 217 and adds to the clinical value of CYP genotyping. CYP1A2 variants constitute genetic risk factors for the development of drug-induced TD as suggested by positive association findings.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…No study mentioned conducting specific tests for population stratification even though six 57,60,87,96,102,103 were known to include patients with different ethnic backgrounds. A minority (21/51) of studies [59][60][61][62]66,67,70,72,74,[76][77][78][79]81,82,[85][86][87][88]96,100 reported testing for Hardy-Weinberg equilibrium.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Clinical validity CYP2D6 is arguably the most important CYP450 gene with regard to the metabolism of antipsychotics, with six typical 78 Cross-sectional 99 Japanese CYP2D6 Any typical antipsychotic Scordo et al 80 Cross-sectional 119 Caucasian CYP2D6 Any antipsychotic Culav-Sumic et al 62 Cross 67 Cross-sectional 214 Japanese CYP2D6 Any antipsychotic Lohmann et al 73 Cross-sectional 109 Caucasian (assumed) CYP2D6 Any antipsychotic Liou et al 72 Retrospective 216 Chinese CYP2D6 Any typical antipsychotic Kakihara et al 97 Prospective 41 Japanese (assumed) CYP2D6 Risperidone Tiwari et al 87 Cross antipsychotics (thioridazine, perphenazine, fluphenazine, zuclopenthixol, haloperidol and chlorpromazine) and two atypical antipsychotics (risperidone and, to some extent, olanzapine) metabolized by the enzyme encoded by it. 108 Thus, it is not surprising that most of the clinical validity studies also focused on CYP2D6 where some significant associations between TD and parkinsonism and PM genotype.…”
Section: Analytic Validitymentioning
confidence: 99%
“…Weight gain and metabolic syndrome 0.49-0.7 [144,145] ADRA2A Weight gain and movement disorders 2.5-4.2 [146][147][148] BDNF Weight gain and movement disorders NA [181,182] COMT Tardive dyskinesia 0.24-0.63 [108,123] CYP1A2 Tardive dyskinesia 1.9 [155,156] CYP2D6 Weight gain and movement disorders 1.6-4.4 [158][159][160][161][162][163][164][165] …”
Section: Adra1amentioning
confidence: 99%